"استثمار أموال الوقف بالطرق المعاصرة ودورها في تحقيق الأمن الاجتماعي -دراسة حالة الجزائر- " - بوترعة, رميصاء; خلوط, هناء (University of Eloued جامعة الوادي, 2020)
"تناولنا في هذه الدراسة المعنونة بـ: استثمار أموال الوقف بالطرق المعاصرة ودوره في تحقيق الأمن الاجتماعي –دراسة حالة الجزائر، لتعالج الإشكالية الرئيسية التالية: إلى أي مدى يمكن أن يساهم الوقف في تحقيق الأمن الاجتماعي ؟، وللإجابة عليها قسمنا بحثنا إلى ثلاثة مباحث، حيث اشتمل الأول على الإطار المفاهيمي للموضوع وركزنا فيه على نقطتين جوهريتين: حقيقة الوقف والاستثمار وأحكام استثمار الوقف، وماهية الأمن الاجتماعي، أما الثاني احتوى على آليتين مستجدتين في الوقف بما يحقق الأمن الاجتماعي، وفي الثالث فقد تم عرض تجربة الجزائر وإسهام الوقف في تحقيق الأمن الاجتماعي فيها. وقد أوصت الدراسة بضرورة الاجتهاد في تحقيق الأمن الاجتماعي لما له من دور حيوي وبارز في استثمار أموال الوقف بالطرق المعاصرة. In this study entitled: Investing the endowment funds in contemporary ways and its role in achieving social security - we dealt with the case of Algeria, to address the following main problem: To what extent can the endowment contribute to achieving social security? And to answer it, we had divided our research into three sections, in which The first was on the conceptual framework of the topic, and we focused on two essential points: the reality of the endowment and investment and the provisions for investing the endowment, and the essence of social security, and the second contained two new mechanisms in the endowment for achieving social security, and in the third, the experience of Algeria and the contribution of the endowment to achieving social security in it was presented alsoThe study recommended the necessity of diligence in achieving social security because of its vital and prominent role in investing the endowment funds in contemporary ways.
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: : استثمار الوقف، الأمن الاجتماعي، الصكوك الوقفية، عقد البناء والتشغيل والتحويل (B.O.T).; Key words: endowment investment, social security, endowment sukuk, construction, operation and transfer (B.O.T) contract.